2004
DOI: 10.1017/s1473550404002095
|View full text |Cite
|
Sign up to set email alerts
|

Broad horizons – SETI, SF and education

Abstract: Science fiction (SF) is often perceived as a ‘fringe’ form of entertainment that excites the socially challenged. This misperception detracts from the critical, scientific and interpretive nature of the genre which can be directed into science teaching at school and university levels as an innovative way of exploring the cultural background, politics, leitmotif and themes of society, science and their operation. One example is the ‘alien’ theme in SF; it is perceptually one of the driving factors in the search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
1
0
2
Order By: Relevance
“…Recent findings in astrobiology have become newsworthy and are often featured in popular films and books (Griffiths, 2004), which indicates that there is noticeable interest in astrobiology beyond the science community. Staley (2003) purported that this fascination has to do with ''the great metaphysical questions of astrobiology'' and the expectation that these questions may be answered in the near future; these authors also suggested that topics in astrobiology should be included in all levels of learning, including primary and secondary school.…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings in astrobiology have become newsworthy and are often featured in popular films and books (Griffiths, 2004), which indicates that there is noticeable interest in astrobiology beyond the science community. Staley (2003) purported that this fascination has to do with ''the great metaphysical questions of astrobiology'' and the expectation that these questions may be answered in the near future; these authors also suggested that topics in astrobiology should be included in all levels of learning, including primary and secondary school.…”
Section: Introductionmentioning
confidence: 99%
“…Σημαντική παράμετρος αυτής της προσέγγισης είναι η διάκριση των πραγματικών γεγονότων από τα φανταστικά και τα ζητήματα ψευτο-επιστήμης. Η τάση αυτή, η οποία ισχύει μέχρι σήμερα, αφορά τόσο στις διδακτικές προσεγγίσεις που χρησιμοποιούν κινηματογραφικές ταινίες και τηλεοπτικές σειρές (Baker, 2001, Barnett et al, 2006Kirby, 2000;Mellor, 2003), για την αντιμετώπιση, κυρίως, των παρανοήσεων που δημιουργούνται όσον αφορά στις έννοιες των Φυσικών Επιστημών, όσο και σε αυτές που χρησιμοποιούν κείμενα επιστημονικής φαντασίας, με κυρίαρχο το στοιχείο διερεύνησης των επιστημονικών θεμάτων, ιδεών και εννοιών των Φυσικών Επιστημών (Al-Khalili, 2003, Allday, 2003Baker, 2001;Bixler, 2007;Brake, 2010;Brake & Thornton, 2003a;Bryan, 2009;Bucher & Manning, 2001;Dubeck, 1990;Cruz, 2013;Czerneda, 2006;Fraknoi, 2003;Griffiths, 2003;Griffiths & Brake, 2004;Marks, 1973;NASA, 2005;Raham, 2004;Tag, 2005;Taylor;2003, Theison;.…”
Section: επιστημονική φαντασία και διδασκαλία φυσικών επιστημώνunclassified
“…(Bernan, 2005;Gough, 1989;2008a;Schneider, 2009) . Η κριτική προσέγγιση, επομένως, των ιστοριών βοηθά στο να στοχαστούμε εποικοδομητικά για τις επερχόμενες εξελίξεις και επομένως να ανταποκριθούμε στις κοινωνικές και πολιτισμικές εξελίξεις και τις επιπτώσεις τους σε παγκόσμιο επίπεδο Bell et al 2013;Dimock & Wald, 2002;Galda, & Beach, 2001;Gough, 2003;2008a;Jones, 2010 (Griffiths & Brake, 2004), παρέχοντας, ταυτόχρονα, στους μαθητές τη δυνατότητα να συνδέουν το υπό μελέτη θέμα και με άλλες περιοχές του πολιτισμού (Mueller & Bentley, 2007;Χαλκιά, 2006:35 (Butzow & Butzow, 2000;Cobern & Loving 2001;Healy, 2003;Willison & Taylor, 2006: 26), τα οποία παράγουν διαφορετικά μονοπάτια γνώσης και άγνοιας (Gough, 2006;. Όπως αναφέρει η Haraway, η τοποθέτηση των διηγήσεων των επιστημονικών γεγονότων στον ετερογενή χώρο της επιστημονικής φαντασίας (SF) παράγει ένα «μετασχηματισμένο πεδίο», το οποίο δημιουργεί ένα συνεκτικό σύνολο συνηχήσεων και συντονισμών ανάμεσα σε όλες τις περιοχές και τις συνιστώσες, μέσα στο οποίο καμιά γνωστική περιοχή ή στοιχείο δεν «υπολείπεται» έναντι κάποιου άλλου, αλλά οι πρακτικές γραφής και ανάγνωσης ανταποκρίνονται η μια στην άλλη μέσω ενός συγκροτημένου χώρου (Gough, 1989;Haraway, 1989:5).…”
Section: επιστημονική φαντασία και διδασκαλία φυσικών επιστημώνunclassified